2009 IEEE International Conference on Robotics and Automation 2009
DOI: 10.1109/robot.2009.5152439
|View full text |Cite
|
Sign up to set email alerts
|

Task-level imitation learning using variance-based movement optimization

Abstract: Recent advances in the field of humanoid robotics increase the complexity of the tasks that such robots can perform. This makes it increasingly difficult and inconvenient to program these tasks manually. Furthermore, humanoid robots, in contrast to industrial robots, should in the distant future behave within a social environment. Therefore, it must be possible to extend the robot's abilities in an easy and natural way. To address these requirements, this work investigates the topic of imitation learning of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 19 publications
0
70
0
1
Order By: Relevance
“…We also showed that it allows simultaneous consideration of constraints in joint space and task space [23]. Muehlig et al [24] recently extended the GMR approach to learn bimanual skills by imitation. In this work, the authors used GMR as a compact probabilistic representation of the task constraints which is then used during reproduction by a gradient-based trajectory optimizer.…”
Section: A Related Work and Motivationsmentioning
confidence: 99%
“…We also showed that it allows simultaneous consideration of constraints in joint space and task space [23]. Muehlig et al [24] recently extended the GMR approach to learn bimanual skills by imitation. In this work, the authors used GMR as a compact probabilistic representation of the task constraints which is then used during reproduction by a gradient-based trajectory optimizer.…”
Section: A Related Work and Motivationsmentioning
confidence: 99%
“…The demonstrated sequences may have different numbers of data entries, so we use dynamic time warping again to temporally match each of the normalized demonstrated sequences in S to the mean sequence s ef f , and interpolate so that all have the same number of data entries (lines [8][9][10][11]. Finally, we compute covariances at each corresponding time step across the temporally matched normalized demonstrated sequences (lines 12-13).…”
Section: ) Gather Similarly Initialized Demonstrations (Line 2)mentioning
confidence: 99%
“…We also compared our approach to a recent approach by Mühlig et al [9]. Mühlig's approach also uses dynamic time warping to temporally match demonstrated trajectories, but uses Gaussian mixture models (GMM) to describe learned motions.…”
Section: B Comparison With Prior Artmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental platform used was the Honda Humanoid Research Robot, a 1.20 m sized humanoid robot set up to run autonomously (Mühlig 2009). To enable the robot to detect and follow the tutor's hand movements and the object's position and trajectories, marker-based tracking methods were used.…”
mentioning
confidence: 99%